Transmedia storytelling e seu potencial como recurso de formação do leitor: jataí, uma proporção criativa - Dalbosco, Cleber Nelson (2017)
This work intends to conceive a transmedia storytelling, in order to explore the relationship between teaching and learning through technology, transdisciplinarity and multiple languages. To achieve this purpose, online and offline pieces of media were elaborated from the creative proposition "A Jataí Bee", that could be applied on schools and universities where communication, arts, media is a choice of study. The choice of this bee as a theme of storytelling is due to the wide presence of this specie in all Brazilian territory, that easily adapts and is therefore sighted in urban spaces, where it commonly nests in trees hollow, cracked walls and spaces between roofs. Supporting the development of the creative proposal for this study, we resorted to the narrative understanding and communication as an interdependent relationship. We also observed the characteristics of transmedia storytelling, a terminological definition developed by Henry Jenkins (2008) within the scope of the convergence culture, conceived as a market strategy and persuasion, as a recurring technique used in the advertising universe and campaigns. Because it was a transdisciplinary proposal, questions and elements of different areas were approached, both in the conceptual part -through terminologies and theories from areas such as cinema, communication, cognitive and social psychology, sociology, reading and literature, education , graphic design - as well as related to the universe of creation making use of contemporary technologies, especially in the design of the pieces that are part of this storytelling. They are: audio-visual resources -videos vignette, promotional videos, documentary - and graphic resources of online and offline application - e-flyer, digitized book, poster, newspaper. It was also emphasized the contextualisation of the narrative as an educational resource. For this reason, Lucia Santaella (1994, 2004, 2005, 2007, 2013) was mainly used, among other authors, the readers profiles typification, highlighting, especially the ubiquitous reader. Thus, the objective was to take into account other factors that are contemplated in the dimensions of the Reading and Reader Training line of the Postgraduate Program in Literature of the University of Passo Fundo. Likewise, aspects associated with the context of teaching and learning were studied, observing the need for motivation and will as the first trainning criteria. As a result, the constant need not only to adopt and question technology in the formation of transmedious readers, but also to perceive the potential of technologies in the complementation of training and learning, emphasizing the indispensable presence of the teacher as a central element in the mediation and development of knowledge and of multiple languages.